2011
DOI: 10.1590/s0102-695x2011005000148
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of estrogenic, mutagenic and antimutagenic activity of nemorosone

Abstract: Currently, a wide range of research involving natural products is focused on the discovery of new drugs in many different therapeutic areas. A great number of the synthetic compounds on the market were derived from natural products, especially plants. Nemorosone is the major constituent of the floral resin of Clusia rosea Jacq., Clusiaceae, and in Cuban propolis. In vitro studies have shown cytotoxic activity in this substance against various tumor cell lines, including those resistant to various cytotoxic dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The mutagenic and antimutagenic activity of nemorosone were assessed by the Ames test on Salmonella typhimurium strains (TA97a, TA98, TA100 and TA102), wherein nemorosone did not induce any mutagenic activity; meanwhile, nemorosome exhibited a moderate to strong protective effect (31 and 53% of inhibition, respectively) in association with mutagens in strains TA100 and TA102. Nemorosone induced estrogenic activity detectable by recombinant yeast assay at various concentrations (EEq of 0.41 ± 0.16 nM), concluding with those results that nemorosone could have a chemotherapeutic application in breast cancer research [120].…”
Section: Cubasupporting
confidence: 73%
“…The mutagenic and antimutagenic activity of nemorosone were assessed by the Ames test on Salmonella typhimurium strains (TA97a, TA98, TA100 and TA102), wherein nemorosone did not induce any mutagenic activity; meanwhile, nemorosome exhibited a moderate to strong protective effect (31 and 53% of inhibition, respectively) in association with mutagens in strains TA100 and TA102. Nemorosone induced estrogenic activity detectable by recombinant yeast assay at various concentrations (EEq of 0.41 ± 0.16 nM), concluding with those results that nemorosone could have a chemotherapeutic application in breast cancer research [120].…”
Section: Cubasupporting
confidence: 73%
“… reported that the benzophenone acuminophenone A, which was isolated from Rheedia acuminata , was not mutagenic to several S. Typhimurium strains (TA98, TA100, TA102, TA1537 and TA1538). Similarly, nemorosone was not mutagenic to strains TA97, TA98, TA100 and TA102 , suggesting that other benzophenones, like GFC, do not induce gene mutations.…”
Section: Discussionmentioning
confidence: 97%
“…The ERs agonist activity of nemorosone by RYA was already evaluated by Camargo et al [20] and the results showed an absence of estrogenicity by its benzophenone. These results show that nemorosone does not have the capacity of binding to the ER and mediating the transcription in an agonist away (causing the same effects of the estradiol), but also reduces the capacity of 17 E 2 to exercise this function.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the compound presented antimutagenic activity, reducing DNA damages induced by the antitumoral mytomicin C [20]. In the order to complement the above results, in view of the outstanding antiproliferative potential of nemorosone and the small number of studies published on its mechanisms of action, the aim of the present investigation was to assess the possible capacity of benzophenone to interact with ERs, by RYA and E-screen assays, and to determine, by comet assay, if the compound causes DNA-damage in tumoral and non-tumoral breast cells.…”
Section: Introductionmentioning
confidence: 99%